Safety of oseltamivir during pregnancy: a comparative study using the EFEMERIS database. (11th February 2014) - Beau, A‐B; Hurault‐Delarue, C; Vial, T; Montastruc, J‐L; Damase‐Michel, C; Lacroix, I
<x xml:space="preserve">Abstract</x> Objective To compare pregnancy outcome between women exposed and unexposed to oseltamivir during pregnancy. Design A comparative observational cohort study of women exposed to oseltamivir during pregnancy. Setting A French prescription database (EFEMERIS) that includes data for pregnant women was used. EFEMERIS records prescribed and dispensed reimbursed drugs during pregnancy and pregnancy outcomes in Haute‐Garonne, South West France. Population Women who delivered from 1 July 2004 to 31 December 2010. Methods The study compared exposed and unexposed pregnant women. Two women unexposed to oseltamivir were individually matched, by maternal age, month, and year of delivery, with one women exposed to oseltamivir. Multivariable conditional logistic regression and multivariable Cox proportional hazards regression were used to evaluate associations between each outcome and exposure to oseltamivir during pregnancy. Main outcome measures Pregnancy loss for any cause, preterm delivery, low birthweight, neonatal pathology, and congenital malformation. Results A cohort of 337 (0.58% of women included in EFEMERIS) women exposed to oseltamivir were compared with 674 unexposed women. The risk for pregnancy loss (HR 1.52; 95 % CI 0.80–2.91), for preterm birth (adjusted OR 0.64; 95% CI 0.31–1.27), and for neonatal pathology (adjusted OR 0.62; 95% CI 0.23–1.54) did not differ between exposed and unexposed groups. When exposure during organogenesis was considered, one case of congenital anomaly (2.0%) among 49 exposed women and one case (1.0%) among 99 unexposed women were observed (crude OR 2.00; 95% CI 0.13–32.00). Conclusions There was no significant association between adverse pregnancy outcomes and exposure to oseltamivir during pregnancy.